Proses Berpikir Mahasiswa Berdasarkan Taksonomi SOLO dalam Penyelesaian Masalah Persamaan Diferensial - Arjudin Arjudin; Sripatmi Sripatmi; Muhammad Turmuzi; Dwi Novitasari; Ratih Ayu Apsari (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
This research is an exploratory descriptive with a descriptive quantitative approach or mix-method which aims to analyze the thinking processes of pre-service mathematics students based on the SOLO taxonomy in solving differential equation problems. The subjects were 86 pre-service mathematics students of the fifth semester of the mathematics education study program who were selected using the purposive sampling technique. Meanwhile, data were collected using problem-solving tests and interviews and then analyzed using descriptive and qualitative statistics with the following stages: (1) transcribing test and interview data, (2) coding segmentation, (3) analyzing student thinking processes in solving differential equation problems, and (4) drawing conclusions. The results showed that pre-service mathematics students' thinking levels were at the pre-structural level (6.98%), uni-structural (25.58%), multi-structural (60.47%), and extended abstract (6.98). Meanwhile, there is no one at the relational level in solving the problem. These results indicate that students need to be well supported and facilitated in problem-solving to achieve higher levels of thinking, such as the relational and extended abstract levels.